Pengaruh Variasi Waktu Tahan Kompaksi Terhadap Performa Kampas Rem Dengan Matriks Phenolic Resin - Budianto, Darmawan; , Ir. Bibit Sugito, MT (2016)
Brake pad is one component of a motor vehicle which serves to stop the vehicle speed motorcycle. When the rate of high-speed vehicle brake has an important role , even the safety of the rider depends on the quality of the brake lining . The purpose of this study was to compare the brake with the time variation of compacting with the brand market brake pad Indopart. Researchers will conduct research begins with making a varied canvas of time compacting the material that is fiberglass , aluminum powder , brass powder , graphite , calcium carbonate , barium sulfate , and phenolic resin. After that mix the brake lining material in accordance with a predetermined composition. Then given the pressure while heated ( sintering ) with a load of 7.5 tonnes with the time variation of compaction for 4 minutes , 7 minutes , and 10 minutes later sintering for 60 minutes at a temperature of 200ºC. Then tested friction with a load of 15 kg for 60 minutes with dry test , test the influence of water, with reference to the standard testing SNI 09-2663-1992 then calculated its wear and friction coefficient and hardness tested by using a Durometer tester. From the research that the average wear of the brake pad Indopart lower and better than the brake pad with the time variation of compaction on the friction test for 60 minutes. The coefficient of friction brake on the testing of a dry friction coefficient of friction highest value is the brake with the time variation of compaction 7 minutes of 0.708. And the highest coefficient of friction results in friction testing the effect of water condition is brake Indopart with a value of 0.668. Hardness values Indopart brake better than the brake with the time variation of compaction of 94 Shore D, while the hardness values approaching the brake with the time variation of compaction 10 minutes with a sintering temperature of 200 ° C for 92 Shore D. Keywords : brake pad, compaction time, friction test, hardness